2018
DOI: 10.1007/s10862-018-9671-9
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness and Attitudes toward Aloneness in Belgian Adolescents: Measurement Invariance across Language, Age, and Gender Groups

Abstract: In this study, the factor structure and psychometric properties of a French adaptation of the well-established Loneliness and Aloneness Scale for Children and Adolescents (LACA) was investigated in a French-speaking sample of Belgian adolescents (N = 641; Mage = 14.35, SD = 2.03; 53.4% girls). In addition, measurement invariance analyses across the two main language groups in Belgium (i.e., Dutch-speaking and French-speaking) and across age and gender were conducted on a combined sample of French-speaking and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Good fit for a 4-factor solution was found in two samples of Belgian adolescents [ 112 ]. Additionally, when comparing to more parsimonious models, the 4-factor model was found to be superior in Flemish- and French-speaking adolescents [ 113 , 114 ]. In a sample of Italian adolescents [ 110 ], three items were deleted based on a reliability analysis (one from the parents- and two from the peer-related loneliness subscale), yielding acceptable model fit for the proposed 4-factor model.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Good fit for a 4-factor solution was found in two samples of Belgian adolescents [ 112 ]. Additionally, when comparing to more parsimonious models, the 4-factor model was found to be superior in Flemish- and French-speaking adolescents [ 113 , 114 ]. In a sample of Italian adolescents [ 110 ], three items were deleted based on a reliability analysis (one from the parents- and two from the peer-related loneliness subscale), yielding acceptable model fit for the proposed 4-factor model.…”
Section: Resultsmentioning
confidence: 99%
“…Scalar invariance across gender has been established in several samples of Belgian children and adolescents [ 59 , 112 , 113 , 114 ]. Scalar invariance across age has been established in a sample of Belgian early through late adolescents [ 113 ] and in a sample of Belgian children, adolescents, and freshmen university students [ 114 ]. In a sample of Belgian adolescents, scalar invariance was further established across language, that is, Flemish- and French-speaking adolescents [ 113 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, if individuals with ASD have little access to these complex social skills, it could lead to a worse comprehension of social interactions, and therefore to feelings of rejection and a greater experience of loneliness. Of note, social anxiety was also found to be related to greater loneliness (Danneel et al, 2018 ; Eres et al, 2020 ; Lim et al, 2016 ; Maes et al, 2019 ; Reed et al, 2016 ; White & Roberson-Nay, 2009 ), and this comorbidity was reported twice as much in our sample of individuals with ASD compared to the 22q11DS group, playing a plausible role in explaining the distinct experience of aloneness between the two conditions. Moreover, social anxiety was described by Hintzen et al ( 2010 ) as the discrepancy between the fear of rejection and the desire for social interaction, a pattern that matches what is reported by individuals with ASD in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Danneel, Maes, Vanhalst, Bijttebier, and Goossens [37] 2018 Loneliness and attitudes toward aloneness in belgian adolescents: measurement invariance across language, age, and gender groups δ: no data present in paper; θ: across waves of data collection; η: response categories often (4) sometimes, seldom, never (1); ¥: ranges of 1 year stability correlations across three and four measurement waves in sample 1 and sample 2, respectively.…”
Section: Correlations Between Subscale Scores Across Waves Of Data Comentioning
confidence: 99%